The Influence of Mathematical Creative Thinking Ability in Terms of Learning Styles on the Learning of Compound Interest and Annuities among Students - Muminu, Muminu; Nugraha, Rahmad Agung; Munadi, Munadi (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyse the relationship between students' learning styles (visual, auditory, and kinaesthetic) with mathematical creative thinking skills, and to determine which learning style has the most dominant influence. The research method used is a mixed method, which combines qualitative and quantitative approaches to obtain a more comprehensive understanding. The results of the study indicate that there are variations in students' mathematical creative thinking skills that are influenced by their respective learning styles. Visual, auditory, and kinaesthetic learning styles have been shown to have a significant influence on students' mathematical creative thinking skills. In particular, auditory learning styles have the most dominant influence compared to visual and kinaesthetic learning styles. These findings indicate the importance of understanding students' learning styles to improve their mathematical creative thinking skills. Thus, the results of this study contribute to the development of adaptive learning strategies, in accordance with students' learning styles, in order to support the achievement of optimal learning outcomes.